1977
DOI: 10.1007/bf01964885
|View full text |Cite
|
Sign up to set email alerts
|

Diamine oxidase activity and histamine release in dogs following acute mesenteric artery occlusion

Abstract: Following superior mesenteric artery occlusion and revascularization in dogs all animals died in a circulatory collapse state. However, pretreatment by aminoguanidine, the strong and specific inhibitor of diamine oxidase, accelerated the circulatory break-down significantly and increased the venous plasma histamine concentrattions up to levels which also in normal dogs are effective in the circulatory system. Furthermore, the haematocrit increased significantly more in the aminoguanidine-treated animals than i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

1978
1978
2000
2000

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…mained at normal adult levels (32-63 U/mg protein). DAO activity in the proximal and middle third of the small intestine was albout 20 were <2%. DAO from all tissues measured, other than the intestine, showed no increase with age ( Fig.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…mained at normal adult levels (32-63 U/mg protein). DAO activity in the proximal and middle third of the small intestine was albout 20 were <2%. DAO from all tissues measured, other than the intestine, showed no increase with age ( Fig.…”
Section: Resultsmentioning
confidence: 91%
“…Previous studies have suggested that DAO may play a protective role in intestinal ischemia by metabolizing increased levels of histamine (19,20). In addition to histamiinie, the polyamine precursor putrescine is also a preferred in vitro substrate for DAO.…”
Section: Resultsmentioning
confidence: 99%
“…histamine concentrations were associated with significantly reduced survival times after intestinal ischaemia and reperfusion [7]. To start a programme elucidating the effects of a DAO inhibition in clinical situations, we first investigated the effect of a large number of drugs, commonly used in an intensive care unit, on human and dog intestinal diamine oxidase in vitro.…”
mentioning
confidence: 99%
“…The results reported in this paper show that DAO activity, that is implicated in the terminal catabolism of polyamines [19] and in the regulation of histamine levels under physiological and pathophysiological conditions [20][21][22][23], is influenced in maternal and fetal tissues by an acute intake of ethanol at doses that are not deleterious for the rats [17]. Ethanol caused both in 12-and 18-day pregnant rats similar inhibitory effects on DAO activity in the liver, the principal organ for alcohol metabolism, and in plasma.…”
Section: Discussionmentioning
confidence: 99%